2021
DOI: 10.1101/2021.08.17.21260128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SARS-CoV-2 Alpha variant is associated with increased clinical severity of COVID-19 in Scotland: a genomics-based retrospective cohort analysis

Abstract: Background The Alpha (B.1.1.7) SARS-CoV-2 variant of concern has been associated with increased transmission and increased 28-day mortality. We aimed to investigate the impact of infection on clinical severity of illness, including the need for oxygen or ventilation in a national cohort study. Methods In this prospective clinical cohort study, 1475 SARS-CoV-2 sequences were obtained from patients infected in Scotland, UK between the 1st November 2020 and 30th January 2021 and matched to clinical outcomes as t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…For Alpha versus previous variants, most previous studies have also estimated an increase in severity over extant diversity. A wide variety of end points have been used, 28-day mortality, hospitalisation, and an ordinal scale based around supplemental oxygen[17-27]. Our estimates are consistent with the majority of these studies.…”
Section: Discussionsupporting
confidence: 86%
“…For Alpha versus previous variants, most previous studies have also estimated an increase in severity over extant diversity. A wide variety of end points have been used, 28-day mortality, hospitalisation, and an ordinal scale based around supplemental oxygen[17-27]. Our estimates are consistent with the majority of these studies.…”
Section: Discussionsupporting
confidence: 86%
“…Of particular interest seems to be Q27 * and K68 * stop codons in open reading frame 8 (ORF8), which might play a role in immune evasion (Zhang et al, 2020;Zinzula, 2021). The lineage B.1.1.7 (Alpha) has been associated with evidence of increased hospitalization, mortality, transmissibility, severity, and possible immune evasion with potential implications for reinfection and vaccine effectiveness in patients (Pascall et al, 2021). These findings concern whether the immunity acquired by natural infection or mass vaccination could confer adequate protection against the constantly evolving SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested some controversial differences. Some studies demonstrated that the Alpha variant may increase the risk of ICU admission and the mortality (3,4). Other studies concluded that there were no signi cant differences (5).…”
Section: Discussionmentioning
confidence: 99%
“…Mortality was 2.7 times higher with the Alpha variant than with the presence of the Delta variant. This risk may be related to the fact that the Alpha may be more aggressive (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation